Inequity in physiotherapeutic interventions for children with Cerebral Palsy in Sweden—A national registry study. (30th September 2019) - Degerstedt, Frida; Enberg, Birgit; Keisu, Britt‐Inger; Björklund, Martin
Abstract: Aim: The aim of this study was to investigate the distribution of physiotherapeutic interventions for children with Cerebral Palsy in Sweden from an equity perspective, considering sex, country of birth and geographical region. Method: This national cross‐sectional registry study includes children with Cerebral Palsy aged 0‐18 years who participated in 2015 in the Swedish national quality registry, the Cerebral Palsy follow‐up programme, CPUP. Comparisons and associations between physiotherapeutic interventions and sex, country of birth and geographical regions were conducted using chi‐square and logistic regression analysis, controlling for cognitive level, level of motor function, age group and dominating symptom. Results: Of the 2855 participants, 2201 (79%) had received physiotherapy. Children born in Sweden had 1.60 times higher odds (95% CI 1.10‐2.33) of receiving physiotherapy compared with children born in foreign countries. Distribution of physiotherapeutic interventions differed significantly between geographical regions. No associations between sex and physiotherapeutic interventions were observed. Conclusion: The results of this study indicate inequity in care in Sweden towards children with Cerebral Palsy born in other counties. Further, physiotherapeutic interventions were not equally distributed in different geographical regions of Sweden. Knowledge of inequity is crucial in order to address the problem.